Respiratory Diseases In Population Living Near Cement Manufacturing Facilities (Texas Journal of Medical Science, 2025)
Dust (PM₂.₅, PM₁₀), NO₂, SO₂ and heavy metals (chromium, cadmium, nickel) emitted into the atmosphere by cement production enterprises are one of the main risk factors for the development of respiratory diseases. The study analyzes the incidence of respiratory diseases (ARI, asthma, COPD, silicosis, lung cancer) in the population living near cement plants in Uzbekistan and foreign countries from a hygienic and epidemiological perspective. According to WHO and local statistical data, the risk of respiratory diseases increases by 1.5–2.0 times in areas with PM₁₀ concentrations exceeding 50 µg/m³. In the Akhangaron, Fergana and Navoi regions of Uzbekistan, this indicator exceeds WHO standards and poses a serious threat to the health of the population. The article also develops hygienic recommendations for air monitoring, technological filtration and sanitation measures